A comparison of sensitivity metrics for two-stage ignition behavior in rapid compression machines. (15th November 2017) - Wilson, David; Allen, Casey
Abstract: A rapid compression machine (RCM) multi-zone model is used to simulate the ignition of primary reference fuel (PRF) mixtures that exhibit two-stage ignition behavior. Sensitivity coefficients for each reaction in the PRF mechanism are calculated from four different metrics: (1) first-stage energy release, (2) first-stage pressure rise, (3) first-stage ignition delay time, and (4) total ignition delay time. The sensitivity coefficients are used to provide four unique rankings, and the rankings are compared using Spearman's rank correlation coefficient. Special emphasis is given to comparing the rankings based on first-stage energy release and total ignition delay time. The level of agreement between these two rankings is shown to depend on the reaction conditions. Simulation cases with high peak heat release rates during the first stage of ignition tend to exhibit disagreement in the rankings, indicating that new kinetic information can be obtained by studying first stage energy release in addition to total ignition delay time. Simulations show that the high peak heat release rates are associated with energy release across a broad range of temperatures (range can be in excess of 100 K even for lean conditions). This distribution leads to a discrepancy between sensitivity coefficients calculated for the total ignition delay time and the first-stage energy release. Sensitivity coefficients for the total ignition delay time are characterized by reactivity at the highest temperatures in the RCM, while sensitivity coefficients for the first-stage energy release are characterized by reactivity across the full range of temperatures in the RCM.